Trichinella spp. in wolves (Canis lupus) and red foxes (Vulpes vulpes) of southern Italy - Scarcelli S.; Buono F.; D'Alessio N.; Rea S.; Castaldo E.; Pesce A.; Locantore F.; Fioretti A.; Marucci G.; Sgroi G.; Modry D.; Veneziano V. (Research in Veterinary Science, 2024)
: Trichinella spp. are cosmopolitan parasites that infect a wide range of hosts, with wildlife being the main reservoir of these zoonotic nematodes, especially red foxes (Vulpes vulpes) and wolves (Canis lupus) due to their apex position in the food chain in most European countries. The aim of this study is to investigate the prevalence of Trichinella spp. in these wild canids and their epidemiological role in the Campania region (southern Italy). From 2017 to 2023, the carcasses of red foxes (n = 352) and wolves (n = 41) were collected as part of a health surveillance plan. Muscle samples were analysed individually by artificial digestion and four (1.1%) red foxes and nine (21.9%) wolves tested positive for Trichinella britovi. All Trichinella isolates were identified as T. britovi by multiplex PCR. Statistically significant differences in prevalence were found by province (p-value = 0.05) for red foxes and sampling years (p-value = 0.01) for wolves. The prevalence was lower in red foxes than in wolves, probably due to the longer life expectancy of wolves compared to red foxes and the role of wolves as apex predators compared to red foxes as meso-carnivores. The results obtained confirm the important role that these wild canids play in the circulation of the parasite.